Theoretical study on the binding selectivity of 18-membered azacrown ethers with alkaline earth metal species - Saprini Hamdiani; Lalu Rudyat Telly Savalas; Agus Abhi Purwoko; Saprizal Hadisaputra (Chemistry Education Program, the University of Mataram, 2018)
The binding selectivity of 18-membered azacrown ethers (monoaza- N1, diaza- N2, triaza- N3, tetraaza- N4, pentaaza- N5, and hexaaza-18-crown-6 N6) with Ca2+, Sr2+, Ba2+ have been studied by density functional theory (DFT) calculations. The complex binding selectivity was analyzed in term of interaction energies, thermodynamic properties, second order interaction energies, and charge transfer effects. The geometrical study shows that Ca2+ and azacrown complexes acquire envelope like structure, leading to shorter bond lengths. As a result, these complex systems have the highest interaction energies. Theoretical study also showed that N6 complex with alkaline earth metal ion were shown to be more stable complex than those ligand with lower nitrogen number. The interaction energy order is N0 < N1 < N2 < N3 < N4 < N5 < N6. This trend shows that the presence of more nitrogen on the crown ether cavity increases the interaction energies by approx. 7.3 % in going from N0 to N6. It is clearly showed that the contribution of the number of nitrogen play a dominant role in the binding selectivity of these systems.